ANALISA KANDUNGAN LOVASTATIN, PIGMEN DAN CITRININ PADA FERMENTASI BERAS IR-42 DENGAN MUTAN Monascus purpureus [Analysis of Lovastatin, Pigments and citrinin in Rice which fermented by Monascus purpureus mutant] - Nurhidayat, N (BERITA BIOLOGI, 2012)
The need of medicine product are increasing now.The fermentation of rice by using Monascus purpureus produce lovastatin, pigments and citrinin as secondary metabolites. The aim of this study was to know the concentration of lovastatin, red and yellow pigments and citrinin in rice which fermented by Monascus purpureus that had been mutated by using ultraviolet irradiation.Three strains were used in this research, such as AsK, yellow Jmba and red Jmba.The result were analyzed by using HPLC and Spectrofotometer.The result showed that the yellow Jmba strain which treated by UV mutagenesis for 3 minutes contain higher lovastatin (1.798%) and pigment and lower citrinin (0.019%) compare to without mutagenesis.On the other hand ASK strain produced higher lovastatin (1.903%) but higher citrinin (1.270%).This research is expected to provide scientific information to the public.That M. purpureus contained lovastatin that is beneficial,red and yellow pigments for natural food colorant.